1997
DOI: 10.1093/hmg/6.12.2173
|View full text |Cite
|
Sign up to set email alerts
|

Prelingual Deafness: High Prevalence of a 30delG Mutation in the Connexin 26 Gene

Abstract: Prelingual non-syndromic (isolated) deafness is the most frequent hereditary sensory defect. In >80% of the cases, the mode of transmission is autosomal recessive. To date, 14 loci have been identified for the recessive forms (DFNB loci). For two of them, DFNB1 and DFNB2, the genes responsible have been characterized; they encode connexin 26 and myosin VIIA, respectively. In order to evaluate the extent to which the connexin 26 gene (Cx26) contributes to prelingual deafness, we searched for mutations in this g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
459
2
15

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 593 publications
(519 citation statements)
references
References 12 publications
25
459
2
15
Order By: Relevance
“…Approximately 12% of these individuals were identified as having mutations in the GJB2 gene responsible for the hearing loss. This frequency is lower than previously reported frequencies, suggesting a unique population, small numbers, or that the frequency in newborn samples may be lower because the study included milder cases [Denoyelle et al, 1997;Zelante et al, 1997]. The discrepancy in frequency of GJB2 mutations in these studies underscores the need for further study and proper classification of cases.…”
Section: Introductioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Approximately 12% of these individuals were identified as having mutations in the GJB2 gene responsible for the hearing loss. This frequency is lower than previously reported frequencies, suggesting a unique population, small numbers, or that the frequency in newborn samples may be lower because the study included milder cases [Denoyelle et al, 1997;Zelante et al, 1997]. The discrepancy in frequency of GJB2 mutations in these studies underscores the need for further study and proper classification of cases.…”
Section: Introductioncontrasting
confidence: 64%
“…To date, 79 loci for nonsyndromic hearing loss have been identified: 40 autosomal dominant, 34 autosomal recessive, and 5 X-linked [Hereditary Hearing Loss Homepage, 2003]. Multiple studies have shown that mutations in the single GJB2 gene may account for up to 50% of nonsyndromic sensorineural autosomal recessive hearing loss or 20% of all childhood hearing loss [Denoyelle et al, 1997;Zelante et al, 1997;Cohn et al, 1999;Green et al, 2002]. The GJB2 gene encodes the connexin 26 protein, which is involved in gap junction formation allowing cell-to-cell diffusion and the transfer of ions between neighboring cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent mode of inheritance of nonsyndromic hearing loss is autosomal recessive (AR) (75-80% of cases). [2][3][4] AR nonsyndromic hearing loss (OMIM 220700) typically has a congenital or prelingual onset. 4 The degree of AR nonsyndromic hearing loss is usually severe or profound, although varying degrees of residual hearing can be observed in a subset of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsyndromic forms are grouped in autosomal dominant (DFNA), autosomal recessive (DFNB), X‐linked (DNFX) and mitrochondrial subtypes. The most commonly affected gene causing nonsyndromic hearing loss (both in autosomal recessive DFNB1A [MIM 220290] and in autosomal dominant DFNA3A [MIM 601544]) is gap junction beta 2 ( GJB2 , [MIM 121011]), the gene encoding the connexin 26 protein (CX26) (Kelsell et al, 1997; Denoyelle et al, 1997). Depending on the studied population, 20–50% of all recessive nonsyndromic SNHL cases can be attributed to a mutation in GJB2 (Hilgert et al, 2009a; Linden Phillips et al, 2013).…”
Section: Introductionmentioning
confidence: 99%